Simulação numérica do processo de erosão do solo em dutos submarinos - Teixeira, Bianca de Pley Almeida (2019)
Submarine pipelines are considered to be the most efficient means of oil and gas transportation in ocean engineering. However, the presence of the structure in a marine environment may change the flow pattern in its immediate vicinity. This change in flow around the structure normally causes the local sediment transport to increase which lead to soil erosion, also known as the scouring process. This work aims to implement a mathematical model for the simulation of the scouring process in submarine pipelines. In order to achieve this goal, the work was divided into 2 stages. Initially, the influence of the seabed proximity in single phase flow around a fixed cylinder was studied. In the second stage, the phenomenon of scouring was studied. The results of the first stage showed good agreement with the experimental results available in the literature and it was possible to determine important numerical parameters, such as computational domain size, mesh size and turbulence model, which were applied in stage 2 of the study. The results of the second stage showed different trends for the erosion equilibrium depth in relation to the sediment transport regime variation. For the clear-water regime a tendency to underestimate the erosion equilibrium depth was observed. For the live-bed regime, which is a more critical regime, there was an overestimation of the depth of erosion. The chosen methodology allowed the implementation of the sediment transport model, considering both the terms due to the bed load and the suspension load, in ANSYS Fluent, a commercial software, which by default does not have such an implemented model.